Aplicação da análise Custo-Volume-Lucro como ferramenta de gestão de custos: um estudo de caso em uma empresa de horticultura de Urucará/AM - Olimpio, Stanley Willanmy Coelho (2023)
This research applied the Cost-Volume-Profit (CVL) method in a horticulture company with the objective of analyzing financial performance and assisting managerial decision-making. The collection of information involved an interview with the owner, addressing the operation of the company, production process and associated costs. The analysis focused on the main indicators: Contribution Margin (MC), Break-Even Point (PE), Operating Leverage Degree (GAO) and Margin of Safety (MS). The results showed that the company operated successfully, surpassing its break-even point, with emphasis on the high contribution margin of the products and the degree of operating leverage. This research highlighted the effectiveness of CVL in analyzing the financial performance of horticulture businesses, providing valuable insights for managerial decision-making. In addition, he highlighted the importance of cost management, showing how the identification and detailing of costs can help in evaluating the company's performance.